Modified Kenaf Bast Fibre Mat Reinforced Biopolymer Composite Enhanced With Spent Coffee Ground Microfiller - Bairwan, Rahul Dev (2024)
The escalating concern over the harmful effects of discarded plastics on the environment has prompted the development of eco-friendly 'green' polymers. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a type of environmentally friendly polymer known for its biodegradability and renewability. However, its mechanical performance is somewhat restricted. Enhancing it can be achieved by combining it with natural fibers to produce green composites. These composites not only provide improved mechanical properties but also maintain biodegradability. In this study, an eco-friendly biocomposite is developed using PHBV and chemically modified non-woven kenaf bast fibers with Propionic anhydride (to improve the fiber/matrix interface and moisture resistance). The initial investigation was conducted on the optimum modified bast fiber loading reinforced PHBV composite. Composites were prepared through the compression molding of a matrix powder, with modified bast fiber mats interleaved within. The incorporation of 30% bast fiber mats into PHBV resulted in significant overall enhancement of properties. Subsequently, this study also explores the utilization of Spent Coffee Grounds (SCG), a residual product of the coffee industry as microfiller particles. These particles as microfillers are introduced into PHBV at varying particle sizes and concentrations (1%, 3%, 5%, and 7%) to create different PHBV-incorporated SCG particle variations. These variations were prepared using hot compression molding machine.